PENERAPAN MODEL PEMBELAJARAN PROBING QUESTION (PPQ) UNTUK MENINGKATKAN KREATIVITAS SISWA DI KELAS TINGKAT SEKOLAH DASAR - Ummu Kulsum; Abdul Munib (Jurnal JPSD (Jurnal Pendidikan Sekolah Dasar), 2017)
Probing question is a tool to ask questions to students that are done periodically. Then the probing question is modified into a learning model using cognitive field bloom theory and kipling theory known as 5W + 1H as a means of learning in the classroom. The purpose of the probing question model is to apply the question periodically to the student in answering the question. While the method used qualitative methods and data analysis used is data reduction, display data and verification to find the findings in the class. after doing field research for elementary school students class IV and V, the results of the findings can from UH (Deuteronomy) is the student profile is rhombic. While the cognitive domain of students into categories competence of knowledge, understanding and application in the Teaching and learning process in the classroom.